The application of the responsive regulation theory on indirect tax compliance among small and medium enterprises in Malaysia / Soliha Sanusi … [et al.] - Sanusi, Soliha; Omar, Normah; Mohd Sanusi, Zuraidah; Muslichah, Istyakara (Universiti Teknologi MARA, 2021)
Tax collection is significant for many countries worldwide to cater for their development and social responsibility expenses. Hence, compliance in terms of tax payment from the taxpayers is essential to have a high tax collection. Due to that, this research aimed to deliver empirical evidence on elements that affect indirect tax compliance among small and medium enterprises (SMEs) in Malaysia from the perspective of the Responsive Regulation Theory. A mixed-method approach on 379 SMEs and regulators was used. It was followed by supporting pieces of evidence from the qualitative part of the research using interviews. The study found evidence to support that long-term tax compliance is best accomplished through voluntarism factors such as level of tax knowledge, availability of integrated technology within firms, and motivation in firms. The study contributes to theoretical implications in the taxation area in which the Responsive Regulation Theory stipulates that in the long run, compliance is best achieved through factors related to voluntarism.